Dystocia due to fetal monstrosity: Monocephalus conjoined twin relieved by partial percutaneous fetotomy in a sheep– A case report - Praveen, S; Kumar, Nithish; Lavanya, Maharajan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Conjoined twin monsters are usually monozygotic twins in origin that failed to undergo complete division at the primitive streak stage of the embryo (Noden and Lahunta, 1985). The incidence of congenital defects in embryonic duplications is common in bovines ranging from 1 in 50,000 to 100,000 normal births followed by sheep and goats (Unver et al. 2007). Anterior duplication is more common than posterior duplication. The etiology of defects in embryonic duplications is attributed to genetic causes, environmental causes and their interactions (Mazzullo et al., 2003). The monsters resulting from congenital defects in embryonic duplications are of clinical concern as they impose a potential threat to dam survivability in addition to fetal loss and associated economic loss to the farmer.